2015
DOI: 10.2298/sarh1510590m
|View full text |Cite
|
Sign up to set email alerts
|

Suicides among Serbian war veterans: An autopsy study

Abstract: The results of this research may give useful information about the individuals with the highest suicidal risk in order to alleviate the consequences of war psychotraumas in veterans and prevent their growth into a permanent handicap or suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The possible explanations for this unfavorable trend during this period in males include the devastating effects of civil wars, the economic and political sanctions, the collapse of the economy, the hyperinflation of the national currency, the notable drop in general living standard, the poor quality of health services (shortage of drugs, medical equipment, together with a large number of wounded individuals, decreasing hospitalization rates, particularly for people aged ≥ 60 years), the influx of more than a million refugees and social disintegration all generated circumstances where suicide prevention and management presented a significant challenge in medical practice[ 63 , 64 ]. The autopsy protocols of all 44 suicides committed by war veterans in the capital Belgrade over the 1991-2000 period showed that 27.3% of veterans had posttraumatic stress disorder, 9.1% had major depression and 6.8% had schizophrenia, while most suicides (84.1%) were committed by recruits of the Yugoslav National Army who spent 3-8 mo in the zone of war operations[ 65 ]. Contrary, among migrants of the Balkan wars in Sweden during the 1991-2001 Balkan wars, in comparison to other European migrants in Sweden during the same period, the risk of death from somatic diseases and psychiatric disorders, particularly post-traumatic stress disorder, was elevated, while the risk of suicide was reduced[ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible explanations for this unfavorable trend during this period in males include the devastating effects of civil wars, the economic and political sanctions, the collapse of the economy, the hyperinflation of the national currency, the notable drop in general living standard, the poor quality of health services (shortage of drugs, medical equipment, together with a large number of wounded individuals, decreasing hospitalization rates, particularly for people aged ≥ 60 years), the influx of more than a million refugees and social disintegration all generated circumstances where suicide prevention and management presented a significant challenge in medical practice[ 63 , 64 ]. The autopsy protocols of all 44 suicides committed by war veterans in the capital Belgrade over the 1991-2000 period showed that 27.3% of veterans had posttraumatic stress disorder, 9.1% had major depression and 6.8% had schizophrenia, while most suicides (84.1%) were committed by recruits of the Yugoslav National Army who spent 3-8 mo in the zone of war operations[ 65 ]. Contrary, among migrants of the Balkan wars in Sweden during the 1991-2001 Balkan wars, in comparison to other European migrants in Sweden during the same period, the risk of death from somatic diseases and psychiatric disorders, particularly post-traumatic stress disorder, was elevated, while the risk of suicide was reduced[ 66 ].…”
Section: Discussionmentioning
confidence: 99%